PARENTING MODEL IN THE ESTABLISHMENT OF CHILDREN’S SOCIAL BEHAVIOR - Hesti Ariestina; Umdzatul Atiqah (Jurnal Lensa Pendas, 2022)
This study aims to determine the model of parenting that is carried out by parents for their children in Plataran Hamlet, where this parenting model supports the success of parents in shaping children's social behavior. This study uses a qualitative method, this method is carried out to determine the appropriate parenting model for shaping children's social behavior. data collection by interview, observation and documentation. Data analysis used descriptive qualitative, namely the presentation in written form and explained what it was in accordance with the data. Checking the validity of the data in this study used source triangulation and time triangulation. The results obtained indicate that the parenting model in instilling children's social behavior has been implemented. The parenting style used by the parents in Plataran Hamlet is more dominant in the democratic parenting pattern, while the authoritarian parenting style is also used. There are two supporting factors, namely internal factors including the family environment, the establishment of children. external factors, namely formal education and non-formal education. There are two inhibiting factors, namely internal factors and external factors, namely the child's self, the family's economic situation. External factors are unfavorable environment and technological progress.